State Policies in the Anglo-Saxon model of Press - Aguado Guadalupe, Guadalupe; Sanmartí Roset, Josep María; Magallón Rosa, Raúl (Estudios sobre el Mensaje Periodístico, 2012)
Besides the language, the countries of Anglo-Saxon culture largely share a similar origin for their respective systems of the press and a democratic and entrepreneurial frame without identified interruptions. On the other hand, each country has followed a different evolution mainly marked by the relations between the State and the Press. From this angle, the United States has been the country less interventionist, followed by Britain. Ireland and Australia, by contrast, have implemented laws and regulations designed to combat such diverse areas as libel, slander, the publication of official secrets or business concentration. Without doubt, the new challenges posed by digital media and the global economic crisis are forcing a review of these four national models.
Keywords: U.S. Media; Press in Britain; Press in Australia; Press in Ireland; Anglo-Saxon press model.